Demand for Forest Products in India : Past Trends and Projections to 2010 - Sharma, Vijay P.; Kumar, Arvind (Indian Forester, 1999)
This paper provides a brief summary of the results of growth performance and projections of demand for forest products in India and uses these results to provide a background for discussion of implications for forest policy and management. The trends indicate that the production of most forest products grew slightly at slower growth rates than its consumption. The growth rates for production and consumption of many products during 1981-94 have been lower than for 1970-80 period. The model used to forecast the demand and supply offorest products performed satisfactorily in terms of goodness offit and its predictability. The forecasts of demand and supply showed a deficit of all types offorest products at national level; except for wrapping and packaging paper and paper board, which was sufficient for the next one and half decades. Demand for forest products is likely to increase from current levels, but the rate of increase is likely to be lower than in the past. Moreover, the forest products and the raw material required to produce them will change with changes in the market and the substitutes of these products. Therefore, the national forest policy and management should take into account all these changes and their effect on extent and composition of demand for forest products.